Fables. [22], Farewell - Willingham, Bill (DC Comics/Vertigo, 2015)
The "Eisner Award-winning series sees the conclusion of the beloved stories of Bigby Wolf, Rose Red, Boy Blue, Pinnochio and countless other timeless fables. The only question left to be answered is whether or not they will have a happy ending."--Provided by publisher.